Improving the properties of kenaf reinforced polypropylene composite by alkaline treatment - Nurain, Mohd Salehudiin; Nurjannah, Salim; Rasidi, Roslan; Nurul Huda, Abu Bakar; Siti Noorbain, Sarmin (Elsevier Ltd, 2023)
Natural fibre composites are widely utilized to make composite materials like textiles, furniture, cars, and buildings. This is due to the material's qualities, which include lightweight, high strength, and low density. Considering that it can grow in a variety of climates, kenaf fibre is one of the natural fibres that can be used in composite materials. However, the high hydrophilic behavior of kenaf fibre presents a challenge. Consequently, alkaline treatment was used to enhance the kenaf-reinforced polypropylene composite's characteristics. Both extrusion and injection molding were used to produce the composite. A composite without the alkaline treatment was also produced so that the outcomes could be compared. The proportion of used kenaf fibres to polypropylene was 170:30. (g). Thermal analysis, melt flow index (MFI), and water absorption testing was conducted on the composite material. Tensile, flexural, and impact testing were then used to determine the mechanical characteristics of the composite. Scanning Electron Microscope (SEM) and Fourier-Transform Infrared Spectroscopy (FTIR) were used to evaluate the composite. The treated sample's tensile strength was determined to be 0.003 MPa, while the untreated sample's value was 0.002 MPa. Flexural strength increased between the treated sample (6545.49 MPa) and the untreated sample (6405.56 MPa). The treated sample's impact strength was 59.26 J/m as compared to 48.97 J/m for the untreated sample. The results of every test conducted so far have demonstrated that the alkaline-treated composite has better physical and mechanical properties than the untreated.